Mathematical Knowledge and Divine Mystery: Augustine and his Contemporary Challengers - Boyer, Steven D. (Christian scholar's review, 2015)
Christians have been active in philosophy of mathematics in recent years, but Steven D. Boyer and Walter B. Huddell III argue that the classical work of Augustine of Hippo in this field has been largely misunderstood or distorted even by its supposed advocates. This essay corrects that distortion and shows how the traditional Augustinian awareness of God’s incomprehensible mystery allows both a deeply Christian resolution to some perennial issues in mathematical ontology and also a surprisingly productive engagement with a contemporary anti-Christian alternative.